Harmonic fields and Maxwell equations on perforated domains. (March 2020) - Qin, Zengyun
Abstract: In this paper, we study the Dirichlet fields and Neumann fields in a perforated domain Ω ε n with n balls of radius ε removed from a simply-connected domain Ω . Structures of these vector fields are obtained. Asymptotic behavior of the solution to the Maxwell equations in the perforated domain is also examined as the number of the holes increases to infinity.